The stairways to heaven: a model of career choice in sports and games, with an application to chess - Kenn Ariga; Giorgio Brunello; Roki Iwahashi; Lorenzo Rocco (Institute for the Study of Labor (IZA), 2008)
We model individual careers in sports and games from initial entry to eventual exit or success as a discrete-choice, finite-horizon optimization problem. We apply this model to the international game of chess and study cross-country differences in the relative success of players. While we find no evidence that the players in our sample from the ex-Warsaw Pact are more talented than European and American players, there is evidence that they face lower training costs.
Keywords: J24; 330; Occupational choice; sports and games; Berufswahl; Sport; Spielwaren; Erwerbsverlauf; Berufsbegleitende Ausbildung; Kosten; Theorie; Transformationsstaaten; Westeuropa; USA